Diagnoses, problems and healthcare interventions amongst older people with an unscheduled hospital admission who have concurrent mental health problems: a prevalence study - Glover, Alex; Bradshaw, Lucy; Watson, Nicola; Laithwaite, Emily; Goldberg, Sarah E.; Whittamore, Kathy H.; Harwood, Rowan H. (BioMed Central, 2014)
Background Frail older people with mental health problems including delirium, dementia and depression are often admitted to general hospitals. However, hospital admission may cause distress, and can be associated with complications. Some commentators suggest that their healthcare needs could be better met elsewhere. Methods We studied consecutive patients aged 70 or older admitted for emergency medical or trauma care to an 1800 bed general hospital which provided sole emergency medical and trauma services for its local population. Patients were screened for mental health problems, and those screening positive were invited to take part. 250 participants were recruited and a sub-sample of 53 patients was assessed by a geriatrician for diagnoses, impairments and disabilities, healthcare interventions and outstanding needs. Results Median age was 86 years, median Mini-Mental State Examination score at admission was 16/30, and 45% had delirium. 19% lived in a care home prior to admission. All the patients were complex. A wide range of main admission diagnoses was recorded, and these were usually complicated by falls, immobility, pain, delirium, dehydration or incontinence. There was a median of six active diagnoses, and eight active problems. One quarter of problems was unexplained. A median of 13 interventions was recorded, and a median of a further four interventions suggested by the geriatrician. Those with more severe cognitive impairment had no less medical need. Conclusions This patient group, admitted to hospital in the United Kingdom, had numerous healthcare problems, and by implication, extensive healthcare needs. Patients with simpler conditions were not identified, but may have already been rapidly discharged or redirected to non-hospital services by the time assessments were made. To meet the needs of this group outside the hospital would need considerable investment in medical, nursing, therapy and diagnostic facilities. In the meantime, acute hospitals should adapt to deliver comprehensive geriatric assessment, and provide for their mental health needs.